2012
DOI: 10.12693/aphyspola.121.1079
|View full text |Cite
|
Sign up to set email alerts
|

Specific Heat of the Ce(Ni1 - xCux)4Mn Compounds

Abstract: Specic heat of the Ce(Ni1−xCux)4Mn compounds has been studied. The samples are prepared by induction melting and it is found, based on the X-ray diraction, that all the compounds keep the CaCu5-type structure. This series exhibits a transition between the ferromagnetically ordered CeNi4Mn and the spin-glass CeCu4Mn compounds, which is well visible in the measurements of the ac susceptibility peak as a function of the magnetic eld frequency and in the magnetization relaxation. In the present research we explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In the previous study [1,2] we have shown for CeCuNi 3 Mn that the Cu substitution develops a spin-glass (SG) state. To further investigate this SG behaviour we have now prepared a number of samples in the series Ce(Cu x Ni 1−x ) 4 Mn.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study [1,2] we have shown for CeCuNi 3 Mn that the Cu substitution develops a spin-glass (SG) state. To further investigate this SG behaviour we have now prepared a number of samples in the series Ce(Cu x Ni 1−x ) 4 Mn.…”
Section: Introductionmentioning
confidence: 99%